Case Study: Postruth Construction During The Covid 19 Pandemic - Edy Subali; Enie Hendrajat (Journal of Development Research, 2022)
This study aims to propose post truth as one of the constructions of transhumanism. To make it easy to understand, the research took case studies in cyberspace related to Covid-19 in Indonesia. Fairclough's critical discourse analysis method is used to analyze post truth on Instagram social media. The results show that post truth as a construction of transhumanism has several arrangements. First, there is a post truth agent, namely the implementing party or subject who does post truth, this shows that the existence of digital technology makes humans have an ambivalent identity. Second, momentum, in this case of the covid pandemic and hot issues (disputes between regional leaders as the time for discourse to appear), momentum is the key that post truth can occur. This shows that technology is used to understand how we co-create human experience. Finally, people who concentrate on digital technology and cyberspace currently operate with the logic of surveillance capitalism, meaning that everything is measured by the number of clicks, engagement, and the duration of the audience watching. We believe that these results have the potential to cause bias in the truth of information to the public, so this study suggests that public authorities should take all the necessary measures to enhance the literacy public to mitigating the negative impacts caused due to the post truth.